(untitled) - Hoskins, B. (Oxford, 2000)
The "Let's Go" readers feature the characters and follow the syllabus of the series of the same name, but can also be used independently. There are two stories per reader, with each one recycling language from the student's book in different contexts. Word counts increase per story and per level for a gradual build-up of reading skills. The stories are illustrated in colour, engaging children's attention and helping comprehension. New words (not in the student's book) are featured in a convenient, on-the-page picture dictionary. Comprehension questions at the end of each story reinforce grammar and skills development. An answer key for both stories is provided at the end of the book
Keywords: English language,Readers (Primary); Study and teaching,Foreign speakers